2002
DOI: 10.1002/etc.5620211010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on cadmium toxicity, speciation, and accumulation during naphthalene biodegradation

Abstract: Lowering pH of a microbiological medium from 7 to 4 decreased cadmium toxicity during naphthalene biodegradation by a Burkholderia sp. Cadmium speciation and cadmium accumulation in the system were studied to explain this effect. Cadmium speciation was determined by direct measurement and by geochemical modeling. Previous studies have implicated the monovalent hydroxylated cadmium (CdOH+) species in the effect of pH on cadmium toxicity. Modeling analysis predicted CdOH+ formation only at very low concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 27 publications
1
22
0
1
Order By: Relevance
“…However, more studies are recommended regarding the different chemical forms of the metals that surpassed the permissible limits to better understand their toxicity. Cobbett and Goldsbrough (2002) stated that neutralization of some metals is potentially achieved when they are associated to proteins, and may be eliminated from an organism by different metabolic routes (Sandrin andMaier 2002, Flora et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, more studies are recommended regarding the different chemical forms of the metals that surpassed the permissible limits to better understand their toxicity. Cobbett and Goldsbrough (2002) stated that neutralization of some metals is potentially achieved when they are associated to proteins, and may be eliminated from an organism by different metabolic routes (Sandrin andMaier 2002, Flora et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…(Sandrin and Maier 2002), in C. regularis (Sakaguchi et al 1979), and in Klebsiella pneumonia (Rudd et al 1983); and/or c) the speciation of the metal in question to a more or less toxic form (Babich and Stotzky 1985;Collins and Stotzky 1992;Ivanov et al 1997). Data from one of the studies described above (Franklin et al 2000) suggest that even relatively small changes in pH (e.g., from 6.5 to 5.7) can reduce metal toxicity.…”
Section: Approaches To Increasing Biodegradation In Co-contaminated Ementioning
confidence: 99%
“…It was reported that forty percent of hazardous waste sites on the U. S. Environmental Protection Agency's national priority list (NPL) are co-contaminated with organic and heavy metal pollutants (Benin et al, 1999;Cheng, 2003;Sandrin and Maier, 2002). Common heavy metal contaminants include arsenic, cadmium, chromium, copper, lead, mercury, nickel and zinc, which present numerous health dangers to higher organisms and are also known to decrease plant growth, ground cover and have a negative impact on soil microflora (Garbisu and Alkorta, 2001;McGrath et al, 2001).…”
Section: Introductionmentioning
confidence: 99%